Acute effects of the RAMP warm-up on sprint and jump performance in youth soccer players - Girginer, F. G.; Seyhan, S.; Açar, G.; Bilici, M. F.; Bilici, Ö. F.; Soylu, Ç. (Frontiers in Physiology, 2025)
Introduction: Pre-competition warm-ups play a critical role in optimizing athletic performance and minimizing injury risk. This randomized, controlled crossover study investigated the acute effects of the Raise, Activate, Mobilize, and Potentiate (RAMP) warm-up protocol on key performance parameters in young male soccer players.